: HIGH SPEED MULTICAST DISTRIBUTION SCHEME FOR MOBILE ADHOC NETWORKS USING DATA MINING TECHNIQUE (International Journal of Engineering and Computer Science, 2017)
To secure multicast communications, security services such as authentications data integrity, access control and group confidentiality are required   The proposed algorithm several key distributions approaches proposed multicast clustering is dividing the groups in to several sub groups ,an entity called Local Controller (LC) manage each subgroup which is responsible for local key management within the cluster. Thus ,after Join or Leave procedures ,only members with in concerned cluster are affected by re-keying process ,the local membership dynamism of a cluster does not affect the other cluster of the group This concept is established in This paper by using one of the Data Mining  Techniques Viz Clustering